2022
DOI: 10.1007/s11547-022-01516-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating solitary brain metastases from high-grade gliomas with MR: comparing qualitative versus quantitative diagnostic strategies

Abstract: Purpose To investigate the diagnostic efficacy of MRI diagnostic algorithms with an ascending automatization, in distinguishing between high-grade glioma (HGG) and solitary brain metastases (SBM). Methods 36 patients with histologically proven HGG (n = 18) or SBM (n = 18), matched by size and location were enrolled from a database containing 655 patients. Four different diagnostic algorithms were performed serially to mimic the clinical setting where a rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Voicu et al compared four algorithms evaluating both conventional qualitative MRI features and quantitative analyses of DWI and DSC PWI parameters in NEPAs. The study confirmed that, among the quantitative parameters, the mean-normalized relative CBV and the mean CBV percentage recovery in NEPAs were more accurate than the ADC in the discrimination of HGGs from BMs, with cutoffs of 1.46 (sensitivity: 83%, specificity: 89%, AUC: 0.904) and 87.5% (sensitivity: 88.9%, specificity: 94.4%, AUC: 0.907) [98]. The quantitative algorithm based on PWI and DWI values had better diagnostic performance than the qualitative approaches, where the radiologists were asked to give the diagnosis solely on the basis of morphological information, and the semi-quantitative algorithm, where radiologists were also helped in the diagnosis by PWI and ADC values based on cutoffs derived from the literature.…”
Section: Multiparametric Approaches Diagnostic Algorithms and Tumor S...supporting
confidence: 65%
See 1 more Smart Citation
“…Voicu et al compared four algorithms evaluating both conventional qualitative MRI features and quantitative analyses of DWI and DSC PWI parameters in NEPAs. The study confirmed that, among the quantitative parameters, the mean-normalized relative CBV and the mean CBV percentage recovery in NEPAs were more accurate than the ADC in the discrimination of HGGs from BMs, with cutoffs of 1.46 (sensitivity: 83%, specificity: 89%, AUC: 0.904) and 87.5% (sensitivity: 88.9%, specificity: 94.4%, AUC: 0.907) [98]. The quantitative algorithm based on PWI and DWI values had better diagnostic performance than the qualitative approaches, where the radiologists were asked to give the diagnosis solely on the basis of morphological information, and the semi-quantitative algorithm, where radiologists were also helped in the diagnosis by PWI and ADC values based on cutoffs derived from the literature.…”
Section: Multiparametric Approaches Diagnostic Algorithms and Tumor S...supporting
confidence: 65%
“…The quantitative algorithm based on PWI and DWI values had better diagnostic performance than the qualitative approaches, where the radiologists were asked to give the diagnosis solely on the basis of morphological information, and the semi-quantitative algorithm, where radiologists were also helped in the diagnosis by PWI and ADC values based on cutoffs derived from the literature. Additionally, the quantitative algorithm was the algorithm with the best concordance with histologic findings [98].…”
Section: Multiparametric Approaches Diagnostic Algorithms and Tumor S...mentioning
confidence: 99%
“…36 patients with histologically proven HGG or solitary BM matched by size and location. [38] Study of 1 H-MRS to differentiate primary and secondary brain neoplasms.…”
Section: Mrimentioning
confidence: 99%
“…Solitary BM and GBM can exhibit quite similar MRI features, such as post-contrast ring enhancement, necrotic core, and large peritumoral edema presenting with high signal on T2-weighted and FLAIR images [ 47 ]. Differentiating these two entities is essential, considering they are the most common brain tumors in the adult population and have quite different treatments [ 47 ].…”
Section: Lesion Detection and Differential Diagnosismentioning
confidence: 99%
“…Solitary BM and GBM can exhibit quite similar MRI features, such as post-contrast ring enhancement, necrotic core, and large peritumoral edema presenting with high signal on T2-weighted and FLAIR images [ 47 ]. Differentiating these two entities is essential, considering they are the most common brain tumors in the adult population and have quite different treatments [ 47 ]. Thus, several researchers have focused on this topic, showing the advantages of multiparametric MRI [ 48 , 49 ] and, more recently, evaluating the performances of different AI-based classifiers compared to expert neuroradiologists.…”
Section: Lesion Detection and Differential Diagnosismentioning
confidence: 99%